Effects of Birth Delivery Mode and Antibiotic Use on Gut Microbiota in Preterm Newborns: A Cohort Study - Fatiha, Raji; Kenza, Hattoufi; Houssain, Tligui; Sobha, El Ftouh; Jaafar, Heikel; Hassan, Aguenaou; Amina, Barkat (International Journal of Child Health and Nutrition, 2025)
Background: The establishment of the gut microbiome begins very early in life. Bacterial colonization is influenced by several factors, especially the mode of delivery and antibiotic intake. In this study, we examined the composition of the neonatal gut microbiota within the first three weeks after birth, focusing on the impact of delivery mode and antibiotic use. Methods: This cohort study included 29 preterm newborns recruited between the first and second day of life at the National Reference Center for Neonatology and Nutrition. Stool samples were collected from diapers and stored at 4°C for up to 6 hours before being stored at -80°C until analysis. The gut microbiota was identified using RT-PCR targeting four phyla: Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria. Results: The comparison of gut microbiota by delivery mode shows that the microbiota of newborns delivered by cesarean section was less diverse than that of those delivered vaginally. During the first 48 hours of life, Enterobacteriaceae, including Escherichia coli, were predominantly present in vaginal births, while Enterococcus spp. (25%), Staphylococcus spp. (20%) and Lactobacillus spp. (5%) were present only in vaginal births. From the second week onwards, Bacteroides fragilis (15%) and Bifidobacterium spp. (10%) were mainly present in vaginal births. By the end of the third week, Enterobacteriaceae and Enterococcus spp. were present in all newborns. All newborns received empiric antibiotic therapy upon admission, with 41% receiving antibiotics for more than 5 days. Conclusion: This study made it clear that microbiota requires time to progress inside the newborn's intestine, depending on the birth mode, either natural or cesarean section.